Kinerja Terminal Penumpang Tipe B Arjasa Masa Pandemi Covid-19 - Rizqi Choirul Wahdana; Nunung Nuring Hayati; Sonya Sulistyono; Willy Kriswardhana; Dano Quinta Revana (Universitas Jember, 2022)
Arjasa Terminal in Jember Regency is a Type B passenger terminal that functions to serve public passenger vehicles for inter-city transportation within the province (AKDP), city transportation (ANGKOT), and public passenger cars (MPU). The Covid-19 pandemic has forced activities at the terminal to experience many limitations, such as limited operational period, limited maintenance budget to limitations in providing passenger services. The existing condition of the observation data shows that some facilities are lacking to reach the standard. The purpose of this study was to determine the condition and completeness of the facilities at the terminal to meet the minimum service standards of PM No. 40 of 2015 during the Covid-19 pandemic. Evaluation of the level of satisfaction of service users with their facilities is carried out using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) analysis methods. Based on the results of observations, 16 indicators (41%) were fulfilled from a total of 39 indicators. The CSI value of the facility is only 75.6% (Poor). While the IPA results obtained 6 quadrants I variables which are the main priority for improvement, 5 quadrant II variables that need to be maintained, 5 quadrant III variables which are a low priority for improvement, and 2 quadrant IV variables whose performance is excessive so it should be reduced. The results of CSI and IPA observations can be used as a basis for improving the operations and services of the Arjasa Terminal entering the post-Covid-19 pandemic. ABSTRAK Terminal Arjasa di Kabupaten Jember merupakan terminal penumpang Tipe B berfungsi melayani kendaraan penumpang umum untuk angkutan antar kota dalam provinsi (AKDP), angkutan kota (ANGKOT), serta mobil penumpang umum (MPU). Pandemi Covid-19, memaksa aktivitas pada terminal mengalami banyak keterbatasan, seperti: keterbatasan masa operasional, keterbatasan anggaran pemeliharaan hingga keterbatasan dalam pemberian pelayanan penumpang. Kondisi eksisting dari data observasi memperlihatkan beberapa fasilitas kurang untuk mencapai standarnya. Tujuan penelitian ini adalah untuk mengetahui kondisi dan kelengkapan fasilitas di terminal terhadap pemenuhan standar pelayanan minimum PM No. 40 Tahun 2015 masa pandemi Covid-19. Evaluasi tingkat kepuasan pengguna jasa terhadap fasilitasnya dilakukan menggunakan metode analisis Customer Satisfaction Index (CSI) dan Importance Performance Analysis (IPA). Berdasarkan hasil observasi menunjukkan terpenuhinya 16 indikator (41%) dari total 39 indikator. Nilai CSI fasilitas hanya 75,6% (Kurang Baik). Sementara hasil IPA diperoleh 6 variabel kuadran I yang menjadi prioritas utama untuk perbaikan, 5 variabel kuadran II yang perlu dipertahankan, 5 variabel kuadran III yang merupakan prioritas perbaikan rendah dan 2 variabel kuadran IV yang kinerjanya berlebihan sehingga sebaiknya perlu dikurangi. Hasil observasi CSI dan IPA dapat digunakan sebagai dasar dalam peningkatan operasional dan pelayanan Terminal Arjasa memasuki masa pasca pandemi Covid-19.